Drip irrigation using a PLC based adaptive irrigation system - Shahidian, S. (2009)
Most of the water used by man goes to irrigation. A major part of this water is used to irrigate small plots where it is not feasible to implement full-scale Evapotranspiration based irrigation controllers. During the growth season crop water needs do not remain constant and varies depending on the canopy, growth stage and climate conditions such as temperature, wind, relative humidity and solar radiation. Thus, it is necessary to find an economic irrigation controller that can adapt the daily water application to the plant needs. The dramatic development of Programmable Logic Controllers, PLCs, and their rather affordable price has made it possible to use them as stand-alone irrigation controllers. In this paper a PLC is used to adapt the daily irrigation amount to actual ETc, using a Hargreaves-Samani type equation. This equation only requires temperature values to calculate Evapotranspiration. Once the ETc is calculated, then the PLC manages the irrigation according to the characteristics of the field, the irrigation equipment and the growth stage of the crop. First year results are very encouraging and indicate a 12% saving in irrigation water. It was also found that heat flux form the soil can influence canopy temperature.